Treatment options for DOCK8 deficiency‐related severe dermatitis. Issue 9 (27th May 2021) - Ollech, Ayelet; Mashiah, Jacob; Lev, Atar; Simon, Amos J.; Somech, Raz; Adam, Etai; Barzilai, Aviv; Hagin, David; Greenberger, Shoshana
Abstract: Background: Cutaneous manifestations of dedicator of cytokinesis 8 gene (DOCK8) deficiency, a combined type of T and B cell immunodeficiency, previously designated as autosomal recessive hyper IgE syndrome, includes dermatitis and skin infections. There are limited treatment options for dermatitis related to the syndrome. Objective: To describe a cohort of patients with DOCK8 deficiency with a focus on the treatment of their cutaneous manifestations. Methods: A retrospective study on all children with the genetic diagnosis of DOCK8 deficiency treated at the Sheba Medical Center between 1/1/2003 and 1/1/2021 was preformed. Collected data included: demographic features, family history, laboratory, genetic testing, skin manifestations, treatment, and disease course. Description of two cases of severe recalcitrant dermatitis treated with dupilumab is detailed. Results: Nine children with a genetic diagnosis of DOCK8 deficiency were included, of whom six were girls (66%) with a median age of 8.5 (±2.2 SD) years. The median age at diagnosis was 2.8 (±2.6 SD) years. Six patients were born to consanguineous parents. Five out of six patients who received hematopoietic stem cell transplantation (HSCT) had a complete response, and one was recently transplanted. Of note, two patients, while awaiting HSCT, were treated with dupilumab for their severe dermatitis resulting in a marked improvement of the cutaneous manifestations and pruritus. Conclusions: Hematopoietic stem cell transplantation is the gold standard and most effective therapy for patients with DOCK8 deficiency. Dupilumab, a biological therapy indicated for atopic dermatitis and other Th2 derived dermatoses, is an excellent option for dermatitis in patients with DOCK8 deficiency and can be used as a bridge before HSCT. Larger studies are needed to confirm this observation.